2020
DOI: 10.1111/1471-0528.16113
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ experiences of care following the loss of a baby at the margins between miscarriage, stillbirth and neonatal death: a UK qualitative study

Abstract: Objective To explore the healthcare experiences of parents whose baby died either before, during or shortly after birth between 20 +0 and 23 +6 weeks of gestation in order to identify practical ways to improve healthcare provision. Design Qualitative interview study. Setting England through two parent support organisations and four NHS Trusts. Sample A purposive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
15

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 13 publications
1
40
0
15
Order By: Relevance
“…However, hospital support was not universal and in a smaller number of cases seemed to be reliant on gestational age when parents’ grief is not necessarily governed by this (Brier, 2008; Obst et al, 2020b). Similar experiences have been identified in miscarriage research; compared to later‐gestation stillbirth, parents have reported lower levels of care and a lack of recognition for their baby (Emond et al, 2019; Smith et al, 2020). Regardless of the baby's gestational age, the birthing experience and care should be consistent and prioritise respect for the baby.…”
Section: Discussionmentioning
confidence: 63%
“…However, hospital support was not universal and in a smaller number of cases seemed to be reliant on gestational age when parents’ grief is not necessarily governed by this (Brier, 2008; Obst et al, 2020b). Similar experiences have been identified in miscarriage research; compared to later‐gestation stillbirth, parents have reported lower levels of care and a lack of recognition for their baby (Emond et al, 2019; Smith et al, 2020). Regardless of the baby's gestational age, the birthing experience and care should be consistent and prioritise respect for the baby.…”
Section: Discussionmentioning
confidence: 63%
“…Given the exploratory nature of the research, interviews took a semistructured approach with open-ended questioning. Interview questions were developed based on previous pregnancy loss studies [26][27][28], including the findings of the larger research programme [25]. A pilot interview assessed the proposed interview schedules' suitability: no changes were required.…”
Section: Study Sample and Settingmentioning
confidence: 99%
“…Seven studies had a distress protocol in place due to the sensitiveness of the topic [20,30,31,[46][47][48][49]. Conversely, twentythree did not mention if they had such protocol in place [21][22][23][24][25][26][27][28][29][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. Sixteen studies declared they had no con ict of interest [20-22, 28, 29, 33, 36, 38, 41-44, 46-49] and fourteen did not mention this [23-26, 30-32, 34, 35, 37, 39, 40, 45, 49].…”
Section: Quality Of Included Studiesmentioning
confidence: 99%